Daily Weather Conditions and Anticipated Death from Cancer - Young Saing KIM; Dong Kyun PARK; In Cheol HWANG; Hong Yup AHN (Tehran University of Medical Sciences, 2018)
Background: The effect of weather conditions on human health has been documented. However, the role of daily weather on anticipated death remains unclear. This study aimed to evaluate the relationship between daily weather conditions and death in terminally ill cancer patients. Methods: We retrospectively searched a medical database of 935 consecutive terminally ill cancer patients who passed away in the palliative care unit from Oct 2009 to Sep 2013. We used Poisson regression to assess the relative risk (RR) of anticipated death based on various weather variables, using mean values calculated from the 10 d around the time of death. Results: The final study population consisted of 745 patients with a mean age of 65.9 ± 12.2 yr. The mean palliative prognostic index (PPI) score in the last week of life was 8.0 ± 3.8. After adjustment for age, sex, cancer type, and PPI score, RRs were 1.69 (95% CI, 1.17-2.46) for low temperature, 2.57 (1.77-3.77) for high diurnal temperature variation, 2.35 (1.61-3.36) for low humidity, and 1.75 (1.22-2.53) for high levels of sunlight. Conclusion: Weather conditions may be a predictor of death in terminally ill cancer patients.